Achieving Pregnancy Using Primary Care Interventions to Identify the Fertile Window - Bouchard, Thomas P.; Fehring, Richard J.; Schneider, Mary M. (Frontiers in Medicine, 2018)
Abstract Objective: To determine the effectiveness of achieving pregnancy with focused intercourse in the fertile window identified using natural fertility indicators. Methods: 24-cycle prospective effectiveness study Setting: A North American web-based fertility monitoring service Participants: 256 North American women aged 20-43 (mean age 29.2 years) seeking to achieve pregnancy. Intervention: Participants identified their fertile window with either electronic hormonal fertility monitoring, cervical mucus monitoring, or both, and recorded their observations on an online fertility-tracking system. Main outcome measures: Pregnancies were validated by nurses with an online self-assessed pregnancy evaluation form. Survival analysis was used to determine pregnancy rates. Results: There were 150 pregnancies among the 256 participants with an overall pregnancy rate of 78 per 100 women over 12 menstrual cycles. There were 54 pregnancies (68%) among the 80 women using the fertility monitor, 11 pregnancies (46%) among the 24 women using mucus monitoring, and 90 (63%) among the 143 women using both mucus and monitor. The 12-cycle pregnancy rates per 100 women were 83 (monitor group), 72 (mucus group), and 75 (mucus and monitor group). Pregnancy rates reached 100% at 24 cycles of use for those women using the hormonal fertility monitor. Conclusion: Use of the hormonal fertility monitor alone seems to offer the best natural estimate of the fertile phase of the menstrual cycle for women wishing to achieve a pregnancy. Focusing intercourse through 24 menstrual cycles can be beneficial for achieving pregnancy.